Association of ORMDL3 and IKZF3 expression with the IL2RA rs2104286 risk variant in relapsing-remitting multiple sclerosis - Stefanović, Milan; Stojković, Ljiljana; Kolić, Ivana; Đorđević, Ana; Dinčić, Evica; Stanković, Aleksandra; Živković, Maja (Archives of Biological Sciences, 2026)
Paper description: IL-2 affects the expression of lymphocyte function genes Ormdl3 and Ikzf3 implicated in multiple sclerosis (MS). IL2RA rs2104286, a genetic variant strongly associated with MS, affects disease risk by attenuating IL-2 signaling. In 66 relapsing-remitting MS patients and 45 controls, the association of blood mononuclear cell ORMDL3 and IKZF3 mRNA expression levels with rs2104286 were tested, assessed by qPCR. In the MS group, increased expression of target genes, and in controls, lower expression of IKZF3 was associated with the protective G allele. A disease-specific association between rs2104286 and ORMDL3 and IKZF3 gene expression is proposed. Abstract: The genetic variant IL2RA rs2104286 (A>G) is strongly associated with multiple sclerosis (MS) risk. It modulates IL-2 signaling, thereby influencing the expression of lymphocyte function-related genes ORMDL3 and IKZF3 that are implicated in multiple sclerosis pathogenesis. This study aimed to investigate the association of rs2104286 with ORMDL3 and IKZF3 mRNA expression in peripheral blood mononuclear cells (PBMCs) of relapsing-remitting multiple sclerosis (RRMS) patients and controls. The study included 66 RRMS patients and 45 healthy controls from the Serbian population. Genotyping and gene expression analysis were performed using qPCR. In RRMS patients, increased ORMDL3 and IKZF3 mRNA expression was associated with the MS-protective G allele (ORMDL3: P = 0.014, 1.35-fold increase; IKZF3: P = 0.023, 1.38-fold increase). In controls, decreased expression of IKZF3 was associated with the G allele (P=0.038, 0.72-fold change). Sex, disease phase, interferon β therapy, and the ORMDL3 and IKZF3 expression quantitative trait locus (rs12946510) did not influence the association between target gene expression and rs2104286. The overall results suggest a disease-specific association between the IL2RA rs2104286 variant and ORMDL3 and IKZF3 expression. Our findings support the notion that the rs2104286 variant may modulate IL-2 signaling in PBMCs, thereby influencing the expression of the immune-relevant genes ORMDL3 and IKZF3.